A Life Course Approach to Understanding Volunteering Practices Among Ethnic-Racial Minority Immigrants on the US-Mexico Border. Issue 3 (August 2021) - Paat, Yok-Fong
Drawing insights from the life course perspective, this study examined individual and contextual factors that shaped volunteering practices among ethnic-racial minority immigrants across their life course. Using purposive sampling, 40 ethnic-racial minority immigrants at various stages of adulthood (18–65 years old) were recruited from a southwestern U.S. state on the US-Mexico border in 2018 to participate in an in-depth interview to better understand how their personal experiences, ecologies, and life histories influenced their volunteering practices. Grounded Theory Method was used to analyze the data. Overall, the participants' volunteering propensities were influenced by (1) significant life events that served as turning points that motivated their desire to help, (2) linked lives in connection with their personal and professional life domains, (3) human capital and agency that served as their resources in volunteering and access to volunteering opportunities, and (4) the context that made volunteering conducive.